PERAN DAKWAH ISLAM DALAM MENGENDALIKAN KENAKALAN REMAJA - Delima Sari Hasibuan; Aida Rahma Munthe; Hoyrina Siregar (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2026)
This research aims to examine the role of Islamic da'wah in reducing juvenile delinquency in Sihitang Village, a rural community where the majority of the population adheres to Islam. The problem of juvenile delinquency in this village has shown an increasing trend, including brawls, small-scale drug use, and violations of community rules, caused by a combination of internal factors (immature cognitive and emotional development, lack of self-confidence) and external factors (unsupportive family environment, negative peer influence, access to harmful content through media). The research method used is library research, which involves collecting and analyzing data from various written sources such as books, scientific journals, and previous research reports relevant to the topics of da'wah, juvenile delinquency, and the relationship between them. The discussion results show that Islamic da'wah adapted to the needs of adolescents – through tailored halaqah (study circles), educational and entertaining activities (competitions, theater, community service), and skill development programs based on Islamic values – plays an important role in shaping the character of adolescents to be faithful and morally upright. Integrated da'wah efforts involving collaboration between preachers, religious institutions, parents, and the village government have begun to show positive results, with a recorded decrease in juvenile delinquency cases and the emergence of adolescents who are more engaged in community life and have clear life goals. Although there are still challenges such as limited resources, this research proves that Islamic da'wah is not only a tool for spreading religious teachings but also an effective means of creating a supportive environment and guiding adolescents towards the right path.